PRODUÇÃO E CARACTERIZAÇÃO DE COMPÓSITOS DE PEBD/Al ORIUNDOS DE EMBALAGENS LONGA VIDA COM PÓ-DE-BORRACHA DE PNEUS OU NEGRO DE FUMO - (:unkn) unknown (UNIVERSIDADE ESTADUAL DE PONTA GROSSA, 2014)
The most common process for recycling post-consumer carton packages of Long Life type is using a "hydrapulper", this device allows to separate the paper from the waste LDPE / Al. In these material a feature which is not valued is due to the presence of Al which will be explored to provide a more attractive visual appearance to this material. Therefore, it was added to LDPE/Al powder tire rubber (PBP) and an additive containing carbon black (MB-P450c) in an attempt to cause an color contrast with Al furthermore also evaluated the power coverage of LDPE / Al when used to give color to pure LDPE (recycled). Were prepared dilution compositions of LDPE/Al with LDPE (recycled) pure compositions containing 10% and 20% PBP and also compositions with 3% MB-P450c assessed in all these situations the effect of the presence of Polybond 3039 (2%). The samples were evaluated by differential scanning calorimetry (DSC), thermogravimetric analysis (TGA), tensile testing, polarized light optical microscopy with a hot stage ("Hot Stage"), optical microscopy (OM), scanning electron microscopy (SEM) and colorimetry. First proved the presence of contaminations arising in the recycling process, possibly polypropylene (PP) and linear low density polyethylene (LLDPE). The dilution of the waste LDPE/Al with LDPE results in a reduction of the elastic modulus and ductility increase as we increase the concentration of LDPE. It was found that the covering power of LDPE/Al is high for what has been observed in the measurements of L , a and b for the compositions of dilution. The presence of the rubber content of 20% PBP resulted in a reduction of the stiffness of the composite. On the other hand, the addition of 10% PBP shown exert similar influence only the addition of LDPE in the compositions with 75% LDPE/Al in this way from the point of view of mechanical properties the addition of 10% PBP causes a smaller reduction in stiffness and ductility of the composite is advantageous in this respect. Carbon black, added through the additive MB-P450c, resulted in an increase in yield stress and a reduction of toughness, from the point of view of color, carbon black proved to be very effective in reducing the brightness and the value of b . Keywords: Recycling. LDPE / Al. Coloring.
Keywords: reciclagem; PEBD/Al; coloração; recycling; LDPE / Al; Coloring; CNPQ::ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA